Dual drive mode polydopamine nanomotors for continuous treatment of an inferior vena cava thrombus. Issue 41 (5th October 2021) - Fang, Dan; Li, Ting; Wu, Ziyu; Wang, Qi; Wan, Mimi; Zhou, Min; Mao, Chun
Abstract : Based on the synergistic effect of PTT/drugs, a kind of bowl-like mesoporous PDA nanomotor (PDANM) modified by RGD and loaded with UK was prepared for the treatment of inferior vena cava thrombus, and achieved good results. Abstract : It is of great significance to find effective thrombolytic treatments due to the harm caused by thrombosis to human health. Based on the formation mechanism and complex microenvironment of a thrombus, polydopamine nanomotors (PDANMs) modified by the peptide of Arg–Gly–Asp (RGD) and loaded with urokinase (UK) were designed and prepared. A polydopamine (PDA) substrate has a good photothermal conversion effect. Under near-infrared (NIR) light irradiation, it can not only perform photothermal therapy (PTT) on thrombus, but also provide the driving force of PDANMs. Thrombolytic drug UK was loaded in the mesoporous structure of the PDA substrate and can be released at the thrombus site for drug therapy. The modified RGD can target the thrombus site, moreover, benefiting from the guanidine group of l -arginine in the peptide chain, and RGD can interact with reactive oxygen species (ROS) in the thrombus microenvironment to produce nitric oxide (NO). NO not only propelled the movement of nanomotors, but also promoted the growth of vascular endothelial cells to repair damaged blood vessels. The experimental results show that NIR and NO can provide dual driving sources for the nanosystem to achieve continuous and deep penetration of the drug-loaded nanomotors at the thrombus site, while realizing the photothermal and drug synergistic therapy to enhance the therapeutic effect and promote the growth of vascular endothelium cells. This kind of thrombus treatment strategy based on nanomotor drug delivery systems will provide good technical support for the clinical treatment of inferior vena cava thrombus.